Is rat liver affected by non-alcoholic steatosis more susceptible to the acute toxic effect of thioacetamide? - Kučera, Otto; Lotková, Halka; Staňková, Pavla; Podhola, Miroslav; Roušar, Tomáš; Mezera, Vojtěch; Cervinková, Zuzana (International journal of experimental pathology, 2011)
Non-alcoholic fatty liver disease (NAFLD) is the most common chronic condition of the liver in the western world. There is only little evidence about altered sensitivity of steatotic liver to acute toxic injury. The aim of this project was to test whether hepatic steatosis sensitizes rat liver to acute toxic injury induced by thioacetamide (TAA). Male Sprague-Dawley rats were fed ad libitum a standard pelleted diet (ST-1, 10% energy fat) and high-fat gelled diet (HFGD, 71% energy fat) for 6 weeks and then TAA was applied intraperitoneally in one dose of 100 mg/kg. Animals were sacrificed in 24-, 48- and 72-h interval after TAA administration. We assessed the serum biochemistry, the hepatic reduced glutathione, thiobarbituric acid reactive substances, cytokine concentration, the respiration of isolated liver mitochondria and histopathological samples (H+E, Sudan III, bromodeoxyuridine [BrdU] incorporation). Activities of alanine aminotransferase, aspartate aminotransferase and alkaline phosphatase and concentration of serum bilirubin were significantly higher in HFGD groups after application of TAA, compared to ST-1. There were no differences in activities of respiratory complexes I and II. Serum tumour necrosis factor alpha at 24 and 48 h, liver tissue interleukin-6 at 72 h and transforming growth factor β1 at 24 and 48 h were elevated in TAA-administrated rats fed with HFGD, but not ST-1. TAA-induced centrilobular necrosis and subsequent regenerative response of the liver were higher in HFGD-fed rats in comparison with ST-1. Liver affected by NAFLD, compared to non-steatotic liver, is more sensitive to toxic effect of TAA.
Keywords: Animals; dietní tuky; látky reagující s kyselinou thiobarbiturovou; thioacetamid; potkani Sprague-Dawley; Dietary Fats; zvířata; Disease Models, Animal; proliferace buněk; respirační komplex I; Cytokines; cholesterol; Triglycerides; Rats, Sprague-Dawley; triglyceridy; karcinogeny; Cholesterol; Rats; Carcinogens; Male; respirační komplex II; cytokiny; ztučnělá játra; Thioacetamide; Electron Transport Complex I; Electron Transport Complex II; krysa rodu Rattus; Thiobarbituric Acid Reactive Substances; Cell Proliferation; Fatty Liver; mužské pohlaví; játra; modely nemocí na zvířatech; Liver